Vernacular Newar Dwelling- Its Construction Technologies and Vertical Functional Distributions - Suwal, Ram Prasad (SCITECH Nepal, 2020)
This research examines the construction process and the techniques of vernacular residential dwellings of core area of Bhaktapur city. The physical characteristics of the buildings are rich in their heritage. The investigation mainly concentrates on assembly of building structures, scientific justification behind the technologies and the vertical functional use of the building. The paper takes an integrated view of building technologies and materials assembled by builders. This research attempts to improve the technologies applied by the builders by emphasizing the cultural context which enables us to provide an integrated explanation. The behavior of structure and material is kept as the focus of investigation. The different case study buildings are selected from upper Bhaktapur (East) to lower Bhaktapur (West) with an assumption that the knowledge may be generalized to the other buildings as well. The main findings reveal that Newar residential dwellings are constructed of brick masonry with mud mortar and timber. The architecture of traditional dwelling is a product of different professionals. Different structure assembling techniques in different parts of the building, detail information on building materials and functional space allocation and terminologies used in building construction are described because each terminology is a meaningful invention of our past tradition on building construction technology.